The Correlation between self-efficacy and iron tablets consuming of Pregnant Women in Garut District - Puspita, Tantri; Jerayingmongkol, Peranan; Sanguanprasit, Boosaba (Unnes Journal of Public Health, 2019)
Maternal health during pregnancy is important not only for the mothers but also for the infant. Anemia status is a condition that may cause a death against pregnant women. Consuming iron tablet lead pregnant women to prevent anemia. The purpose of this study was to identify the relationship between self-efficacy and consuming iron tablet during pregnancy. This study was a secondary analysis from previous study which included 263 pregnant women in the analysis. The pregnant women were in 5 Public Health Care area in Garut District. The Data were collected using self-administered questionnaire. The result revealed that more than 50 %  participant were confident and highly confident of taking iron tablets. Amount 22% of them were always consumed the iron tablet as they daily supplement. There was moderate correlation between self-efficacy and iron tablet consuming of pregnancy women in Garut District (r =407, α< 0,01). Health care providers are recommended to enhance pregnant women iron tablet consuming by improve their self-efficacy. It also can include their family as their motivator of improving self-efficacy to consume iron tablets.